2003
DOI: 10.1128/jvi.77.21.11733-11744.2003
|View full text |Cite
|
Sign up to set email alerts
|

The AIDS-Like Disease of CD4C/Human Immunodeficiency Virus Transgenic Mice Is Associated with Accumulation of Immature CD11bHiDendritic Cells

Abstract: CD4C/human immunodeficiency virus (HIV) transgenic mice develop an AIDS-like disease. We used this model to study the effects of HIV-1 on dendritic cells (DC). We found a progressive decrease in total DC numbers in the lymph nodes, with a significant accumulation of CD11bHi DC. In the thymus, the recovery of transgenic CD8␣؉ DC had a tendency to be lower. Spleen DC were augmented in the marginal zone. Transgenic DC showed a decreased capacity to present antigen in vitro, consistent with their reduced major his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 86 publications
6
45
0
Order By: Relevance
“…Immature dendritic cells are thought to play an important role in inducing these regulatory suppressor CD4 ϩ T-cell subsets (57). Moreover, dendritic cells from these CD4C/HIV-1 Tg mice were found to have an immature phenotype and to be functionally impaired as disease progresses (48). …”
Section: Discussionmentioning
confidence: 99%
“…Immature dendritic cells are thought to play an important role in inducing these regulatory suppressor CD4 ϩ T-cell subsets (57). Moreover, dendritic cells from these CD4C/HIV-1 Tg mice were found to have an immature phenotype and to be functionally impaired as disease progresses (48). …”
Section: Discussionmentioning
confidence: 99%
“…The availability of CD4C/HIV transgenic (Tg) mice expressing gene products of HIV-1 in immune cells and developing an AIDS-like disease has provided an opportunity to devise a novel model of mucosal candidiasis (12). These CD4C/HIV Tg mice are immunodeficient and exhibit atrophy of lymphoid organs, a preferential depletion of CD4 ϩ T cells, with altered CD4 ϩ T cell proliferation in vitro, loss of CD4 ϩ T cell help, CD4 ϩ T cell and B cell activation and impaired dendritic cell (DC) function (13)(14)(15)(16)(17). In addition, disease of the lung (lymphocytic interstitial pneumonitis), heart (myocytolysis, myocarditis), and kidney (tubulointerstitial nephritis, segmental glomerulosclerosis, microcystic dilatation) develop in these Tg mice (13,18).…”
Section: S Tudies Report Oropharyngeal Candidiasis (Opc)mentioning
confidence: 99%
“…Flow cytometry analysis was performed by gating on CD69 ϩ cells, to determine the percentage of CD4 ϩ T cells expressing each of the cytokines. Bone marrow-derived DCs (BMDCs) were generated using a modification of methods previously described (16,19). BM cells were filtered through a 70-m nylon mesh, washed with HBSS, and cultured with GM-CSF (1000 U/ml; Cedarlane Laboratories) and IL-4 (500 U/ml; Cedarlane Laboratories) in supplemented RPMI 1640.…”
Section: Determination Of Intracellular Cytokinesmentioning
confidence: 99%
“…Analysis of spleen of (CD4C/ Nef 3 Foxp3/GFP) double Tg mice confirmed the increased percentage of CD4 (30). This latter cell subset is known to favor accumulation of Treg (31).…”
Section: Cd8mentioning
confidence: 72%
“…This strongly suggests that Nef is operating independently of these two immune defects known to favor Treg expansion in models of lymphopenia (45,46) or thymic depletion (32) in mice. In addition, results from mixed (Tg:non-Tg) chimeras showed that the relative Treg expansion was observed only in Tg donor cells, but not in non-Tg donor bystander cells, strongly suggesting that Treg dysregulation is unlikely to originate from immature DC known to accumulate in these CD4C/HIV Nef Tg mice (30). The same argument can be used to rule out any circulating factor, such as extracellular Nef (47) or BAFF, which could favor Treg development (48).…”
Section: Y505fmentioning
confidence: 99%